2002
DOI: 10.1046/j.1540-8167.2002.00845.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise is Superior to Pacing for T Wave Alternans Measurement in Subjects with Chronic Coronary Artery Disease and Left Ventricular Dysfunction

Abstract: TWA should be measured during exercise when it is used for clinical risk stratification. EPS results may not be an adequate surrogate for spontaneous events when evaluating new risk stratification tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 16 publications
1
34
0
Order By: Relevance
“…Recent cohort studies that involved at least 100 patients found that T-wave alternans was associated with substantially increased risk and predicted events as well as or better than other markers, including LVEF, electrophysiological testing, SAECG, BRS, and HRV. 97,105,180 -182 Furthermore, T-wave alternans predicted risk in patients with coronary artery disease 181,183 and in patients with dilated cardiomyopathy. 105 In all of these studies, patients not manifesting T-wave alternans were at low risk for SCD.…”
Section: T-wave Alternansmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent cohort studies that involved at least 100 patients found that T-wave alternans was associated with substantially increased risk and predicted events as well as or better than other markers, including LVEF, electrophysiological testing, SAECG, BRS, and HRV. 97,105,180 -182 Furthermore, T-wave alternans predicted risk in patients with coronary artery disease 181,183 and in patients with dilated cardiomyopathy. 105 In all of these studies, patients not manifesting T-wave alternans were at low risk for SCD.…”
Section: T-wave Alternansmentioning
confidence: 99%
“…Although pacing-induced T-wave alternans has been linked to ventricular arrhythmia risk, 182 one head-to-head comparison study found that exercise-induced T-wave alternans was a better predictor. 183 The typical definition for an abnormal T-wave alternans test is the occurrence of Ͼ1.9 V of alternans starting at a heart rate of Ͻ110 beats per minute. Tanno and colleagues, 182 in a study of pacing-induced T-wave alternans, found that increasing the heart rate cutoff can increase the negative predictive value to 100% but at the cost of a lower positive predictive value.…”
Section: T-wave Alternansmentioning
confidence: 99%
“…During atrial pacing, the depolarisation and repolarisation of the ventricles will not differ from exercise, but this method cannot be used in patients with atrial fibrillation and patients with an AV block. Concordance rates between exercise testing and atrial pacing are reported to be between 55% and 81% [11][12][13][14]. Its prognostic value was studied by Rashba et al [13] who found no prognostic value for incidence of death, sustained VA, and appropriate ICD therapy using an atrial paced protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Concordance rates between exercise testing and atrial pacing are reported to be between 55% and 81% [11][12][13][14]. Its prognostic value was studied by Rashba et al [13] who found no prognostic value for incidence of death, sustained VA, and appropriate ICD therapy using an atrial paced protocol. Using a ventricular pacing protocol, patients with atrial fibrillation and AV block can be tested as well.…”
Section: Discussionmentioning
confidence: 99%
“…11 One possible reason is that assessment of ECG TWA by pacing yields a lower rate of positive tests than does assessment by exercise. 25,26 Another reason is that 87% of our patients used beta-blockers, which reduce ECG TWA. 16 Use of beta-blockers was not terminated for this research study, but this did not influence clinical management.…”
mentioning
confidence: 99%